Joined application of a multiaxial critical plane criterion and a strain energy density criterion in low-cycle fatigue - Andrea Carpinteri; Giovanni Fortese; Camilla Ronchei; Daniela Scorza; Sabrina Vantadori; Filippo Berto (Fracture and Structural Integrity)
In the present paper, the multiaxial fatigue life assessment of notched structural components is performed by employing a strain-based multiaxial fatigue criterion. Such a criterion, depending on the critical plane concept, is extended by implementing the control volume concept reated to the Strain Energy Density (SED) approach: a material point located at a certain distance from the notch tip is assumed to be the verification point where to perform the above assessment. Such a distance, measured along the notch bisector, is a function of both the biaxiality ratio (defined as the ratio between the applied shear stress amplitude and the normal stress amplitude) and the control volume radii under Mode I and Mode III. Once the position of the verification point is determined, the fatigue lifetime is assessed through an equivalent strain amplitude, acting on the critical plane, together with a unique material reference curve (i.e. the Manson-Coffin curve). Some uniaxial and multiaxial fatigue data related to V-notched round bars made of titanium grade 5 alloy (Ti-6Al-4V) are examined to validate the present criterion.